The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.18371/fcaptp.v6i41.251527
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization of the Hr-Management System of the Enterprise in the Context of Globalization Changes

Abstract: Аbstrаct. The аrtіcle іs аbоut іnvestіgаtіng аnd fоrmulаtіng methods оf digitalization of the HR-management system of the enterprise in the context of globalization changes by means of HR-technologies and HR-functions transformation analysis. The оbject оf the reseаrch іs the mоdіfіcаtіоn оf the HR-technologies, factors influencing the development of the HR-function in times of digitalization. Reseаrch methоds аre а set оf theоretіcаl аnd methоdоlоgіcаl, ecоnоmіc аnd аpplіed іssues оf defіnіtіоn, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This way, our employees can manage their work from any part of the world in a flexible manner". This appears to be in line with the findings of Melnychenko [8], who suggested that digitalization gives employees greater flexibility to work, which contributes to employee retention. Therefore, it can be written that: Proposition 10.…”
Section: Retentionsupporting
confidence: 91%
See 3 more Smart Citations
“…This way, our employees can manage their work from any part of the world in a flexible manner". This appears to be in line with the findings of Melnychenko [8], who suggested that digitalization gives employees greater flexibility to work, which contributes to employee retention. Therefore, it can be written that: Proposition 10.…”
Section: Retentionsupporting
confidence: 91%
“…The use of co-working spaces demonstrates an appropriate response to globalization and digitalization as employees can collaborate with one another regardless of their location, demonstrating greater employee mobility. Furthermore, the Chinese firms were also found to be actively using digital platforms for remote working to foster flexible working, which contributes to employee retention [8]. This demonstrates not only the impact of the COVID-19 pandemic on retention, whereby remote working emerged as a norm, but also the demographic shifts, as the younger workforce appears to be motivated for greater flexibility and the incorporation of technology.…”
Section: Comparison Of the Findings And Employee Lifecycle Management...mentioning
confidence: 90%
See 2 more Smart Citations
“…The key opportunities that digitalization brings to HR-management have been substantiated. Melnychenko et al, (2021) [33] have stated that to get the most out of advanced technologies, HRcompetencies must be clearly defined, correlated with business requirements, differentiated by functions, roles and levels, updated at the right time and applied to perform any HR-management functions. Digital transformation of HR management systems adds increased value to digital business systems.…”
Section: Technology and Digitizationmentioning
confidence: 99%